Leveling the playing field through school meals - Gelli, Aulo; Aurino, Elisabetta (International Food Policy Research Institute, 2019)
An analysis of learning outcomes from the evaluation of a national school feeding program in Ghana reveals that disadvantaged students benefited most from free school meals. Overall, students with access to school meals had higher academic and cognitive test scores on average compared with students without access to the program, but the program led to much greater gains for certain disadvantaged groups including girls, students from poor households, and students from the Northern regions of Ghana. This evidence suggests that providing free school meals is an effective way to increase opportunities for disadvantaged youth by leveling the playing field through improved educational achievement. However, key structural changes could maximize potential learning impacts resulting from the program. Improvements in program implementation through monitoring the quality and quantity of food served are needed to overcome program implementation challenges identified by the evaluation. Beyond the feeding program itself, investments to improve the quality of education are expected to further improve learning outcomes, especially when school meals incentivize increased school attendance.